Tríades Republicanas: a experiência de elaboração de uma exposição sobre os usos públicos do passado republicano brasileiro no Palácio Tiradentes: Republican Triads: the experience of preparing an exhibition on the public uses of the Brazilian Republican past in the Tiradentes Palace (Revista de História da UEG (REVHIST), 2021)
The present article proposes to report the conception and organization’s experience of the exhibition "130 years of the Proclamation of the Republic: Republican Triads", based at the Tiradentes Palace, current seat of Legislative Assembly of Rio de Janeiro. It seeks here to reflect on the possibilities of the public uses of republican Brazil’s history and its writing by the Palace from its visual dimension and museological activities.Keywords: Public History. Republican Brazil. Uses of past. Tiradentes Palace.